UNC-45A is required for neurite extension via controlling NMII activation - Iizuka, Yoshie; Hellweg, Raffaele; Schütz, Florian (Molecular biology of the cell, 2017)
UNC-45A is a highly conserved member of the UNC-45/CRO1/She4p family of proteins, which act as chaperones for conventional and nonconventional myosins. NMII mediates contractility and actin-based motility, which are fundamental for proper growth cone motility and neurite extension. The presence and role of UNC-45A in neuronal differentiation have been largely unknown. Here we demonstrate that UNC-45A is a novel growth cone-localized, NMII-associated component of the multiprotein complex regulating growth cone dynamics. We show that UNC-45A is dispensable for neuron survival but required for neurite elongation. Mechanistically, loss of UNC-45A results in increased levels of NMII activation. Collectively our results provide novel insights into the molecular mechanisms of neurite growth and define UNC-45A as a novel and master regulator of NMII-mediated cellular processes in neurons.
Gesehen am 11.10.2018